Economic comparison of low-temperature and ultra-low-temperature district heating for new building developments with low heat demand densities in Germany - Best, Isabelle (International Journal of Sustainable Energy Planning and Management, 2018)
District heating risks to lose competitiveness the lower the linear heat density of a district is. The distribution network needs to be highly efficient in order to ensure economic feasibility. The heat distribution temperatures are crucial to keep distribution heat losses as low as possible. For a new development in Germany consisting mainly of single family houses, two district heating networks at different supply temperature levels are examined in terms of economic and efficiency aspects. Depending on the required temperature level and temperature difference between supply and return the needed volume flow differ. Consequently also the required pipe diameter is affected. The impact of design temperature and operating strategy on the economic feasibility of the district heating network is investigated.